'Blu-Tack' as an intravesical foreign body: Overcoming a sticky situation. (November 2016) - Boyle, Jemma M; Cleaveland, Paul; Mokete, Moeketsi
Intravesical foreign bodies can pose a significant urological challenge. An unusual intravesical foreign body described within the literature is 'Blu-Tack'. This unique material with its distinct physical properties presents a particular challenge in its management. We describe our novel endoscopic approach to the removal of an intravesical 'Blu-Tack' mass and suggest this method as a means of facilitating successful extraction of this particular foreign body.